Learning Arabic Language Improves Student's Memorization of the Al-Qur’an - Anni Annisa; Rini Yudiati (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2024)
Learning Arabic for non-Arab people still has many obstacles and problems to face because Arabic is not an easy language to master completely. But studying it is something that cannot be ignored. The need for Arabic for the world community is currently quite high, both for Muslims and non-Muslims.The specificity of the language of the Al-Qur'an has given people enthusiasm and willingness to learn Arabic. The efforts made are to make it easier to memorize the Al-Qur'an. Apart from that, understanding Arabic allows a person to easily understand and understand the contents of the Al-Qur'an. An interest in memorizing the Al-Qur'an and the ability to speak Arabic can be an influence on someone's achievement in memorizing the Al-Qur'an. This research was conducted at Ma'hadRubbaht Al-Futuhat Jepara, Central Java. This research aims to determine the effect of Arabic language mastery and the ability to memorize the Al-Qur'an of Santriwati Ma'had Rubbaht Al-Futuhat Jepara, Central Java.So this research is expected to provide good benefits for Santriwati, namely increasing motivation in memorizing and mastering the Al-Qu'ran, for teachers it is hoped that it can provide benefits in helping provide easy learning motivation for Santriwati in mastering and memorizing the Al-Qu'ran. The research method used is a quantitative approach, namely interview guides, test papers, observation guides and archives.Keywords: Learning, Arabic, Memoriation, Al-Qur'an.